Impaired myocardial performance in a normotensive rat model of intrauterine growth restriction - Menendez-Castro, Carlos; Toka, Okan; Fahlbusch, Fabian; Cordasic, Nada; Wachtveitl, Rainer; Hilgers, Karl Friedrich; Rascher, Wolfgang; Hartner, Andrea (Pediatric Research, 2014)
Intrauterine growth restriction (IUGR) is an important risk factor for cardiovascular disease. Previous studies revealed altered myocardial matrix composition after IUGR. We hypothesized that IUGR is accompanied by compromised myocardial performance independently from arterial hypertension.IUGR was induced in Wistar rats by maternal protein restriction, and hearts of male offspring were studied using echocardiography, immunohistochemistry, real-time PCR, and western blot analysis.At day 70 of life, in the absence of arterial hypertension (mean arterial blood pressure: 101.3 ± 7.1 mmHg in IUGR vs. 105.3 ± 4.6 mmHg in controls, not significant (NS)), echocardiography showed a reduced contractility (ejection fraction: 65.4 ± 1.8% in IUGR vs. 82.2 ± 1.5% in controls, P < 0.001) of a more distensible myocardium in IUGR rats. Altered expression patterns of myosin chains and titin isoforms and increased expression levels of atrial natriuretic peptide, Na/K-ATPase, and ?-adrenergic receptor 1 were detected. A higher number of cardiac fibroblasts and vascular cross-sections were observed in IUGR rats, accompanied by elevated expression of hypoxia inducible factor 1 target genes, such as vascular endothelial growth factor and its receptors.We observed a blood pressure-independent impairment of myocardial function after IUGR, which possibly favors cardiovascular disease later in life. Some IUGR-induced myocardial changes (e.g., sarcomeric components) may partly explain the compromised cardiac performance, whereas others (e.g., elevated vascular supply) reflect compensatory mechanisms.
EVALuna2:3704